Utilization of Neem Leaves as a Biological Pesticide for the Control of Anthrachnose Diseases in Dragons (Hylocereus sp.) - Nolla Dwi Elvira; Yenny Wuryandari (Nusantara Science and Technology Proceedings, 2022)
Dragon fruit (Hylocereus sp.) has problems in its cultivation related to Plant Pest Organisms (OPT). One of the pathogens that attack dragon fruit plants is Colletotrichum sp. which can cause anthracnose. dragon fruit pest control method can be done by using biological pesticides from neem leaf extract. Pesticides from plant extracts are sources of various compounds that are rich in various types of active ingredients such as secondary metabolites that play an important role in the process of interacting or competing and protecting themselves from competitors. The purpose of this study was to determine the effectiveness of neem leaf pesticide for controlling anthracnose on dragon fruit plants. The method used is testing the inhibitory power of neem leaf biological pesticides against anthracnose on dragon fruit plants in vitro. The concentration treatments of biological pesticides included 0%, 20%, 40%, and 60%. The results obtained showed that the biological pesticide neem leaf with a concentration of 20% already had an inhibitory power against the pathogen Colletotrichum sp. which is quite good because at that concentration it already has a fairly high antifungal compound. The magnitude of the inhibitory power of neem leaf biological pesticides at a concentration of 20% was 53.94%.